Pemanfaatan Media Berbasis Mind Mapping dalam Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah 61 Medan - Khusnul Zauharoh (Maslahah: Jurnal Pengabdian Masyarakat, 2022)
The research was conducted with the aim of obtaining information about the influence of-based media Mind Mapping in Islamic Religious Education (PAI) learning during the teaching and learning process. This study uses a qualitative descriptive approach, namely the research process is carried out naturally without any manipulation, according to the conditions that occur in the field. Data collection tools are interviews, observations, and documentation. Observations were made by observing directly the learning activities in schools. The results showed that media was Mind Mapping effective in increasing the creativity and activeness of students, students were very enthusiastic in the learning process in class. The use of Mind Mapping media also helps students concentrate while studying and understand lessons easily